Do human-like designed (anthropomorphism) artificial intelligence (AI) language platforms influence usage intentions among youths? - Chee Hua, Chin; Ivy Yee-Xuan, Kho; Chee Ling, Chin (Emerald Publishing Limited, 2025)
Purpose This study aims to develop a conceptual framework based on technology acceptance model (TAM) to explore the usage intention of artificial intelligence (AI)-language platforms, using data from the context of Sarawak, Malaysia. Specifically, the study seeks to examine the relationship between TAM dimensions (perceived usefulness and ease of use) and quality dimensions (perceived intelligence, perceived accuracy and understandability) on the intention to use AI-language platforms, with the moderating role of anthropomorphism.